Strategic reading 2 : - Richards, Jack C. (Cambridge University Press, 2003)
Strategic Reading is a three-level series designed to develop reading, vocabulary-building, and critical-thinking skills. The Teacher's Manual provides clear step-by-step notes on how to use the Student's Book in class. It includes an overview of the series, a model lesson plan, and detailed vocabulary and teaching suggestions for each unit